Gamma oscillations precede interictal epileptiform spikes in the seizure onset zone - Ren, Liankun; Kucewicz, Michal T; Cimbalnik, Jan; Matsumoto, Joseph Y; Brinkmann, Benjamin H; Hu, Wei; Marsh, W Richard; Meyer, Fredric B; Stead, S Matthew; Worrell, Gregory A (Neurology, 2015)
OBJECTIVE: To investigate the generation, spectral characteristics, and potential clinical significance of brain activity preceding interictal epileptiform spike discharges (IEDs) recorded with intracranial EEG. METHODS: Seventeen adult patients with drug-resistant temporal lobe epilepsy were implanted with intracranial electrodes as part of their evaluation for epilepsy surgery. IEDs detected on clinical macro- and research microelectrodes were analyzed using time-frequency spectral analysis. RESULTS: Gamma frequency oscillations (30-100 Hz) often preceded IEDs in spatially confined brain areas. The gamma-IEDs were consistently observed 35 to 190 milliseconds before the epileptiform spike waveforms on individual macro- and microelectrodes. The gamma oscillations associated with IEDs had longer duration (p < 0.001) and slightly higher frequency (p = 0.045) when recorded on microelectrodes compared with clinical macroelectrodes. Although gamma-IEDs comprised only a subset of IEDs, they were strongly associated with electrodes in the seizure onset zone (SOZ) compared with the surrounding brain regions (p = 0.004), in sharp contrast to IEDs without preceding gamma oscillations that were often also detected outside of the SOZ. Similar to prior studies, isolated pathologic high-frequency oscillations in the gamma (30-100 Hz) and higher (100-600 Hz) frequency range, not associated with an IED, were also found to be associated with SOZ. CONCLUSIONS: The occurrence of locally generated gamma oscillations preceding IEDs suggests a mechanistic role for gamma in pathologic network activity generating IEDs. The results show a strong association between SOZ and gamma-IEDs. The potential clinical application of gamma-IEDs for mapping pathologic brain regions is intriguing, but will require future prospective studies.
Keywords: Seizures; implantované elektrody; mozek; Humans; mikroelektrody; lidé středního věku; Spectrometry, Gamma; epilepsie temporálního laloku; Female; dospělí; záchvaty; lidé; elektroencefalografie; Microelectrodes; spektrometrie gama; Adult; Electrodes, Implanted; ženské pohlaví; Male; Middle Aged; Brain; Epilepsy, Temporal Lobe; Electroencephalography; mužské pohlaví